Alterations in peripheral blood NK cell subsets and function in patients with HBeAg-positive chronic hepatitis B during pregnancy - Shen, Xiaokun; Zhang, Xiaosong; Cao, Yanqiu; Zhang, Li; Yuan, Hongxia; Wang, Haixin; Zhou, Yarui; Diao, Shuo; Qi, Xingshu; Li, Fujie; Fan, Qingjie; Li, Shinan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe majority of patients with chronic hepatitis B (CHB) are in the immune-tolerant phase during pregnancy, exhibiting relatively stable liver disease. However, some hepatitis B e antigen (HBeAg)-positive pregnant women may develop liver dysfunction, a condition with an unclear pathogenesis.MethodsIn this study, we analyzed the phenotype and function of natural killer (NK) cell subsets using flow cytometry and enzyme-linked immunosorbent assay in HBeAg-positive pregnant women, HBeAg-negative pregnant women, and healthy pregnant controls.ResultsWe found that HBeAg-positive pregnant women exhibited a decreased proportion of peripheral blood CD56bright NK cells, which correlated negatively with HBV DNA loads and alanine transaminase (ALT) levels, whereas an increased proportion of CD56dim NK cells correlated positively with HBV DNA loads and ALT levels. CD56dim NK cells in HBeAg-positive women displayed a highly activated phenotype characterized by elevated expression of activating receptors (NKG2D and CD226) and reduced expression of inhibitory receptors (NKG2A and CD158b). Consistent with this phenotype, their CD56dim NK cells demonstrated enhanced cytotoxic capacity by diminished interferon-γ production and enhanced CD107a and granzyme-B production. Furthermore, NK cells from HBeAg-positive pregnant women failed to suppress Th17 cell polarization. This study elucidates alterations in peripheral blood NK cell subsets, phenotypes, and functions in pregnant women with CHB. Collectively, these results indicate that peripheral NK cells in HBeAg-positive pregnant women exhibit a unique profile of activation coexisting with functional impairment.